Characterisation of high added value compounds in wastewater throughout the salting process of codfish ( Gadus morhua ) - Ferraro, Vincenza; Cruz, Isabel B.; Jorge, Ruben Ferreira; Xavier Malcata, F.; Castro, Paula M.L.; Pintado, Manuela E. (Food Chemistry, 2011)
International audience In Portugal Atlantic codfish (Gadus morhua) is dry-salted with food-grade marine salt for 6 days. During this process, codfish incorporates salt and drains away water up to 22%(w/w) of its weight, which contains important compounds, such as free amino acids, peptides and proteins. Hence, the chemical profile of such water, composed of various soluble nitrogen fractions, was thoroughly determined. Along the salting process, the ratio of water released to trichloroacetic acid-soluble nitrogen remained constant, but the proportion between water released and phosphotungstic acid-soluble nitrogen decreased because of proteolysis. The concentration of free amino acids increased from 2.68 g/l to 5.41 g/l within 6 days, but myofibrillar proteins were found to be approximately constant, ca. 3.31 g/l. Creatine, aspartic and glutamic acids, glycine, taurine and tryptophan were the dominant free amino acids, the release of which was successfully modelled. Total biogenic amines concentration in wastewater at the end of the salting process was ca. 100 mg/kg. (C) 2010 Published by Elsevier Ltd.